Assessment of preauthorization and 24-hour expert consultation as a restrictive antimicrobial stewardship bundle in a Brazilian tertiary-care hospital: an interrupted time series analysis - Andréa Beltrami Doltrario; Gilberto Gambero Gaspar; Andrea Queiroz Ungari; Roberto Martinez; Antonio Pazin Filho; Benedito Carlos Maciel; Fernando Bellissimo-Rodrigues; Rodrigo de Carvalho Santana (Elsevier, 2022)
Summary: Background: Worldwide, healthcare facilities face high and often inappropriate consumption of antimicrobials. However, there are limited antimicrobial stewardship (ASP) studies from low- and middle-income countries that include restrictive measures and their impacts on antimicrobial consumption. Aim: This study aims to assess the impact of a restrictive bundle (preauthorization requirements and offering consultation with an infectious diseases physician 24 hours a day) on antimicrobial consumption, in a tertiary hospital in Brazil. Methods: We conducted an interrupted time series analysis (ITS) with pharmacy-based data from January 2010 to December 2018 to evaluate changes of level and slope in antimicrobial consumption (expressed in DDD/1,000 patient-days) after the implementation of the restrictive bundle in September 2014. Fourteen restricted antimicrobials (amphotericin B deoxycholate, liposomal amphotericin B, micafungin, voriconazole, ganciclovir, amikacin, ampicillin/sulbactam, daptomycin, ertapenem, levofloxacin, linezolid, piperacillin/tazobactam, polymyxin B, and tigecycline) and eight unrestricted were analysed. Findings: Among the 14 restricted antimicrobials, four presented a significant negative level change: micafungin (-2,14, p=.027), voriconazole (-14.72, p<.001), ertapenem (-1.89, p=.007) and amikacin (-13.98, p<.001). The only negative slope change was observed for the liposomal amphotericin B, -0.532 (p=.009). The restricted antibiotics group presented an increased consumption trend (1.068, p=.002) compared to the pre-intervention period, a similar change was observed for the unrestricted antibiotics group (1.360, p<.001). Conclusion: Preauthorization and 24 hour expert consultation were partially effective as a restrictive antimicrobial stewardship bundle in a Brazilian tertiary-care hospital. Increased consumption of unrestricted antimicrobials was observed as a side effect of the intervention.